2014
DOI: 10.1038/ncomms4568
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral fullerene with μ3-carbido ligand and titanium-carbon double bond stabilized inside a carbon cage

Abstract: In all metallofullerenes known before this work, metal atoms form single highly polar bonds with non-metal atoms in endohedral cluster. This is rather surprising for titanium taking into account the diversity of organotitanium compounds. Here we show that the arc-discharge synthesis of mixed titanium-lutetium metallofullerenes in the presence of ammonia, melamine or methane unexpectedly results in the formation of TiLu 2 C@I h -C 80 with an icosahedral I h (7) carbon cage. Single-crystal X-ray diffraction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
81
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 60 publications
7
81
0
4
Order By: Relevance
“…In the second one (9 kJ mol À1 higher in energy), the C 2 fragment is tilted out of the M 2 Ti plane,h as m 2 -coordination with Ti and one lanthanide,and m 1 -coordination with another lanthanide.C 2 is likely to exhibit fluxional motion at room temperature.T he structure and dynamics of the M 2 TiC 2 cluster are similar to those of M 3 C 2 clusters in Sc 3 C 2 @C 80 [22] and Lu 3 C 2 @C 88 . [23] M 2 TiC@C 80 -I has ac luster-localized LUMO with large contribution of Ti and af ullerene-based HOMO, [16] and similar spatial distribution of the frontier MOs is predicted for M 2 TiC@C 80 -II. In Lu 2 TiC 2 @C 80 -I, both HOMO and LUMO are predominantly localized on the endohedral cluster and have al arge contribution of the acetylide fragment.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…In the second one (9 kJ mol À1 higher in energy), the C 2 fragment is tilted out of the M 2 Ti plane,h as m 2 -coordination with Ti and one lanthanide,and m 1 -coordination with another lanthanide.C 2 is likely to exhibit fluxional motion at room temperature.T he structure and dynamics of the M 2 TiC 2 cluster are similar to those of M 3 C 2 clusters in Sc 3 C 2 @C 80 [22] and Lu 3 C 2 @C 88 . [23] M 2 TiC@C 80 -I has ac luster-localized LUMO with large contribution of Ti and af ullerene-based HOMO, [16] and similar spatial distribution of the frontier MOs is predicted for M 2 TiC@C 80 -II. In Lu 2 TiC 2 @C 80 -I, both HOMO and LUMO are predominantly localized on the endohedral cluster and have al arge contribution of the acetylide fragment.…”
mentioning
confidence: 64%
“…[15] Recently,i na na ttempt to obtain Ti-based nitride clusterfullerenes with Lu using NH 3 as ar eactive gas or melamine as as olid organic nitrogen source,w eh ave discovered an ew type of clusterfullerene,L u 2 TiC@C 80 , which has an endohedral m 3 -carbide ion and aT i ÀCd ouble bond. [16] Them olecule is an isostructural analogue of Lu 2 ScN@C 80 ,i nw hich the Sc-N fragment is replaced by the isoelectronic Ti = Cfragment. Unfortunately,inthe Lu/Ti/NH 3 and Lu/Ti/melamine syntheses,L u 2 TiC@C 80 is only am inor by-product;t he products are predominantly Lu 3 N@C 2n nitride clusterfullerenes,which precludes further exploration of this new type of clusterfullerenes.H erein we demonstrate that 1) M 2 TiC@C 80 clusterfullerenes can be synthesized with high selectivity for many lanthanides using methane as areactive gas;2)this synthetic route also affords appreciable amounts of another cage isomer of M 2 TiC@C 80 as well as an ew type of clusterfullerenes,M 2 TiC 2 @C 80 ;3 )Dy 2 TiC@C 80 exhibits single-molecule magnet (SMM) behavior, whereas the SMM properties of Dy 2 TiC 2 @C 80 are are less pronounced owing to the presence of the second carbon atom in the central unit.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Popov and co-workers found that a new type of μ 3 -C mixed-metal carbide clusterfullerene, Dy 2 TiC@I h -C 80, also exhibits SMM behavior. [30][31][32] However, the SMM properties of Dy 2 TiC 2 @I h -C 80 are less functional due to the presence of the second carbon atom in the central unit. In this regard, it is also anticipated that new carbide clusterfullerenes with M 2 C@C 2n compositions with unusual properties will be discovered in the near future.…”
Section: Potential Applications Of Clusterfullerenesmentioning
confidence: 99%